Free-Living Nematodes Together With Associated Microbes Play an Essential Role in Apple Replant Disease - Kanfra, Xorla; Liu, Benye; Beerhues, Ludger; Sørensen, Søren J.; Heuer, Holger (Frontiers in Plant Science, 2018)
Apple replant disease (ARD) is a severe problem in apple production worldwide. It is caused by a complex of soil biota, leading to small discolorated roots, as well as increased biosynthesis of phytoalexins, total phenolic compounds and antioxidants. We sampled soil from randomized field plots with either apple trees affected by ARD, which were five times replanted every second year, or with healthy trees growing in plots, which had a grass cover during this period. We investigated the contribution of nematodes to ARD by dissecting the soil biota from plots infested with ARD and non-infested control plots into a nematode and a microbe fraction. Nematode communities significantly differed between ARD and control soil as revealed by high-throughput sequencing of 18S rRNA genes. Plant-parasitic nematodes were too low in abundance to explain root damage, and did not significantly differ between ARD and control soil. Their separate and synergistic effect on ARD symptoms of susceptible M26 apple rootstocks was analysed four and eight weeks after inoculation in three greenhouse experiments. Inoculants were either nematodes from ARD plots (NARD), NARD plus microbes from ARD plots (MARD), NARD plus microbes from control plots (MCon), nematodes from control plots NCon plus MARD, NCon plus MCon, MARD, or MCon, or non-inoculated control. In all three experiments, the combination NARD plus MARD had the strongest adverse effect on the plants, with respect to growth parameters of shoots and roots, total phenolic compounds and phytoalexins in roots, and antioxidants in leaves. NARD also induced ARD but less than NARD plus MARD. NARD plus MCon had delayed effects on the plants compared to NARD plus MARD, suggesting that detrimental nematode-microbe interactions built up with time. Effects of MARD or NCon plus MARD were minor or not distinguishable from those of MCon or non-inoculated control. Overall, the source of the inoculated nematodes -ARD or control soil- and the interaction between ARD nematodes and microbes were highly significant factors determining ARD. In conclusion, exploring the associations of nematodes and microbes in ARD soils will give the chance to unravel the etiology of ARD.